2010
DOI: 10.1002/ejoc.201000246
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate Chemistry: Synthesis of O‐Glycosylated Derivatives of Glucosinalbin

Abstract: The synthesis of the major glucosinolate of Moringa oleifera and of other non‐natural O‐glycosylated derivatives of glucosinalbin is reported. The synthetic sequence applied, which involves the conversion of carbohydrate‐based nitrostyrenes into the key thiohydroximates, appears to be sufficiently versatile to synthesize a range of glucosinolatesbearing a glycosylated phenolic function. We synthesizedanalogues of the naturally occurring L‐rhamnoside 1 with a view to estimating the importance of this phenol‐pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
4
5
0
Order By: Relevance
“…The resulting MIC-1 was analyzed by 1 H- 13 C nuclear magnetic resonance spectroscopy and high-resolution mass spectrometry. The data obtained by the analysis were consistent with those previously reported ( Gueyrard et al, 2010 ) and the structure of MIC-1 was confirmed to be correct ( Figure 1A ).…”
Section: Methodssupporting
confidence: 90%
“…The resulting MIC-1 was analyzed by 1 H- 13 C nuclear magnetic resonance spectroscopy and high-resolution mass spectrometry. The data obtained by the analysis were consistent with those previously reported ( Gueyrard et al, 2010 ) and the structure of MIC-1 was confirmed to be correct ( Figure 1A ).…”
Section: Methodssupporting
confidence: 90%
“…As a consequence, the isothiocyanate may be better taken up by herbivores or be transported over longer distances in the soil, thereby potentiating the effect of glucomoringin conversion products on pathogens and herbivores in the plant's environment. Current attempts to synthesize different glycosylated forms of sinalbin, including glucomoringin, may help to assess the role of side-chain glycosylation on the biological effect (Gueyrard et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in many tropical countries extracts of the leaves, seeds and roots of Moringa tree species, belonging to the family Moringaceae, are used for a large range of medical uses (Eilert et al, 1981;Kumar et al, 2010). The main glucosinolate found in this tree is 4-(α-L-rhamnosyloxy) benzyl glucosinolate or glucomoringin, a rhamnose derivative of sinalbin (Amaglo et al, 2010;Bennett et al, 2003;Gueyrard et al, 2010;Mekonnen and Drager, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…“Specialist” plants, which can be considered for convenient isolation of one specific GL in reasonable amount, are in very limited number [ 11 , 12 , 13 ]. This is particularly the case for thiofunctionalized GLs, for which the synthetic approach should be privileged to make available attractive substrates for biological studies [ 14 , 15 ]. Nevertheless, since our pioneering work [ 16 ], only a small number of syntheses have focused on GLs bearing an external thio-function in the aglycon part.…”
Section: Introductionmentioning
confidence: 99%